The Impact on Consent in the Crime of Sexual Assault: Analysis of Cases of Alcohol Intoxication of the Victim - Bohorquez Guevara, Mary Yomalisi (2026)
This article examines a relatively recent issue: the impairment of consent in cases of sexual assault within contexts involving alcohol consumption. In particular, it analyzes situations in which a victim, after voluntarily consuming alcoholic beverages, experiences a diminished capacity to freely consent to a sexual act. The study seeks to determine whether consent given by a person under the influence of alcohol may still be regarded as free, informed, and voluntary in the context of sexual relations, even when the alcohol consumption itself was voluntary. Furthermore, based on the premise that consent is a gradable concept, the article identifies three categories of cases that reflect varying degrees of impairment of consent in such contexts. Finally, the article argues that individuals engaging in sexual relations with a person under the influence of alcohol must pay attention to certain indicators that may reveal whether that person’s decision-making capacity is impaired to a degree that invalidates consent, thereby creating a potential risk of criminal liability for sexual assault.